2018
DOI: 10.1007/s11587-018-0362-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of dengue versus chikungunya outbreaks in Costa Rica

Abstract: For decades, dengue virus has been a cause of major public health concern in Costa Rica, due to its landscape and climatic conditions that favor the circumstances in which the vector, Aedes aegypti, thrives. The emergence and introduction throughout tropical and subtropical countries of the chikungunya virus, as of 2014, challenged Costa Rican health authorities to provide a correct diagnosis since it is also transmitted by the same vector and infected hosts may share similar symptoms. We study the 2015-2016 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Point estimates of key model parameters showed that individuals were being diagnosed at a faster rate for the dengue virus. Both data anomalies suggest that dengue cases were over reported in the 2015–2016 outbreak [7].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Point estimates of key model parameters showed that individuals were being diagnosed at a faster rate for the dengue virus. Both data anomalies suggest that dengue cases were over reported in the 2015–2016 outbreak [7].…”
Section: Resultsmentioning
confidence: 99%
“…In [29], the authors explore a single-outbreak deterministic model with state variables describing the host and vector dynamics of dengue and chikungunya. The estimated parameters were: the transmission rate, the diagnosis rate, the average vector infectious period and the initial value of the susceptible population.…”
Section: Classical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an ample history of mathematical models for vector-borne diseases [44,45,46,47,48,49,50,51,52,53], among others. Moreover, other models specifically on estimating parameters for dengue, chikungunya and Zika include: [53,54,55,56,57,58]. We introduce a nonlinear differential equation single-outbreak epidemic model that describes the Zika dynamics with sexual transmission and host availability for mosquito feeding in Costa Rica.…”
Section: Single Outbreak Modelmentioning
confidence: 99%
“…On the other hand, many of these methods are based on sequential algorithms that allow the approximation of the posterior density using sampling schemes such as rejection sampling, MCMC or sequential Monte Carlo sampling (see [61] for an exhaustive summary of the subject). Some of the parameters were kept fixed in order to follow the ecology constraints of the vector, as well as some conditions of the transmission dynamics of the disease that have been studied in previous articles ( [52], [58]). The total set of parameters (fixed and estimated), as well as the initial conditions of the system are presented in Table 2.…”
Section: Parameter Estimation Using Abcmentioning
confidence: 99%